2019
DOI: 10.1093/milmed/usz171
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation in Pregnant and Postpartum Women Veterans: An Initial Clinical Needs Assessment

Abstract: Introduction Pregnancy and postpartum, or the perinatal period, are times when women are particularly vulnerable to mental health concerns, including suicidal ideation. Risk factors for suicidal ideation during this period of a woman’s life are depression and exposure to trauma, the latter of which may occur during military operations. The number of women veterans in the United States continues to rise, as does their use of maternity benefits. In this pilot study, we examined the feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
4
17
1
1
Order By: Relevance
“…Suicide risk The Columbia-Suicide Severity Rating Scale (C-SSRS) is a clinician-administered interview that assesses suicidal ideation and suicidal behavior over the lifetime and within the last month [48]. This measure is a brief, thorough assessment of suicidal risk that has been found to be reliable and valid across populations [48,49], including in pregnant and postpartum populations [50].…”
Section: Methodsmentioning
confidence: 99%
“…Suicide risk The Columbia-Suicide Severity Rating Scale (C-SSRS) is a clinician-administered interview that assesses suicidal ideation and suicidal behavior over the lifetime and within the last month [48]. This measure is a brief, thorough assessment of suicidal risk that has been found to be reliable and valid across populations [48,49], including in pregnant and postpartum populations [50].…”
Section: Methodsmentioning
confidence: 99%
“…The findings revealed symptoms of prenatal depression were also a risk factor for suicidal ideation, which was consistent with findings in a study on 1517 pregnant women [ 35 ]. Previous researches also showed that suicidal ideation was associated with higher levels of depressive symptoms during prenatal and postpartum period [ 47 , 48 ]. Suicidal ideation of pregnant women is usually assessed in conjunction with maternal depression.…”
Section: Discussionmentioning
confidence: 99%
“…From November 2017 until October 2018, 18 pregnant veterans were recruited from a census maintained by the VA maternity care coordinator. We have previously described recruitment details as part of a larger study ( Szpunar et al., 2020 ). Briefly, written informed consent as well as sociodemographic, medical, obstetrical, and military history were obtained from the participants at the initial encounter during the 3rd trimester of pregnancy, mean 36.4 weeks gestation (SD ​= ​1.8 weeks), and in the postpartum period at 6.7 weeks post-birth (SD ​= ​0.9 weeks).…”
Section: Methodsmentioning
confidence: 99%